INTER-RELIGIOUS HARMONY: THE CHALLENGING VILLAGE FUNDS MANAGEMENT IN THE REGIONS OF SHARIA LAW IMPLEMENTATION - Fanzikri, Mirza (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2024)
AbstractIn accordance with the implementation of village autonomy, village governments face challenges in governing village funds and maintaining inter-religious harmony. This research analyzed the internalization of inter-religious harmony in the region where Islamic Law is implemented and specifically investigated how village administrations sustain inter-religious harmony during the village funds management process. This article also examined religious minoritiesΓÇÖ participation in the village funds management process through the lens of harmony among religious communities. This paper employed qualitative methodology to examine cases from various villages in Banda Aceh City, where the predominant population and all village leaders are Muslim, exhibiting a propensity to allocate village funds exclusively for Muslim activities. At the same time, other religious villagers constitute co-existing minority groups. The researcher identified the case locations in three villages across two distinct sub-districts, focusing on the inter-religious population around worship house distribution areas. The data were assessed by comparing findings from observations, in-depth interviews, and document reviews about village fund administration from 2016 to 2020 through triangulation analysis. The studyΓÇÖs findings indicated that diverse religious minorities participate in village funds management during the planning and implementation phases. Focusing on how to foster inter-religious harmony principles, encompassing tolerance, equality, and collaboration among religious communities, this research elaborated on how the village fund management in Banda Aceh City occurs steadily, lacking dynamism and conflicts among religions.